Does CSR pay off: a Comparison Between Saudi and British Banks in Terms of CSR Practices from a Strategic Perspective. - Saifuddin, Dalal (2011)
While the view of making profits for the shareholders remained the dominant perception among corporates until the late twentieth century, the ideology of corporate social responsibility (CSR hence thereafter) is one of the main areas, which is currently gaining a consistent attention by scholars and business executives worldwide. Moreover, governments, media, customers, activists, NGOs and other stakeholders are putting an increasing pressure on companies to act in a responsible manner. Also, the fierce competition in the marketplace has created a situation in which companies need to consistently seek new ways of differentiation from their competitors. Hence, based on this fact, the ideology of strategic CSR has risen to match such a need of the business. As far as CSR is concerned, there is a strong evidence of the CSR emergence in the western world across different sectors. Namely, the banking industry is one of the main sectors which illustrated a significant contribution in the CSR field. On the other hand, there were number of Saudi banks which have also taken the approach of social responsibility. However, given that the concept of CSR entered the Saudi society recently, there was a vital need to investigate the nature and approach of these practices in comparison to the UK ones. This research aims to determine whether the CSR in the banking sector of Saudi Arabia is strategic or not. In order to do so, it will first investigate the different phases of the history through which the concept of CSR has evolved. Further, the research will explore the current status of the CSR today as well as the drivers of CSR growth in the western world. Also the research will seek to outline the misalignment between CSR practices and business strategies as well as the strategic CSR. this will then be followed by highlighting the best CSR practices in the UK banking sector after providing an enlightenment of what the SAC Framework (socially Anchored Competencies) is exactly about. The UK banks were selected in order to be used as a bench mark against which the Saudi CSR practices will be compared. Finally the research will attempt to utilize its findings and analysis in order to draw a final conclusion about the CSR practices in the Saudi banking sector in light of the UK banks’ responsible initiatives.